Three Cases of Concomitant Intraductal Papillary Mucinous Neoplasm and Pancreatic Neuroendocrine Tumour - Tewari, Nilanjana; Zaitoun, Abed M; Lindsay, Daniel; Abbas, Areeg; Ilyas, Mohammad; Lobo, Dileep N (JOP. Journal of the Pancreas, 2013)
Context Intraductal papillary mucinous neoplasms (IPMNs) are uncommon tumours which can be associated with pancreatic and extrapancreatic malignancies. The association of IPMN and neuroendocrine tumours of the pancreas has been reported previously but is exceedingly rare. Case report We report three cases of IPMN treated with total pancreatectomy/extended distal pancreatectomy. Histopathological analysis of the resected specimens revealed concomitant IPMN and neuroendocrine tumour. Two patients had adenocarcinoma as well. Conclusions The presence of an IPMN may place the entire pancreas at risk of developing other tumour types and vigilance during all stages of management is necessary to ensure optimal treatment. Image: Total pancreatectomy and cholecystectomy.